Effect of Storage Conditions on the Phenolic Content and Antioxidant Properties of Freeze-Dried Bignay [Antidesma bunius (L.) Spreng.] Pomace Extract - Zubia, Claire; Babaran, Gilda Melanie; Reginio, Jr., Florencio; Mopera, Lotis; Israel, Katherine Ann; Navarro, Baby Richard; Elegado, Francisco; Duque, Sheba Mae (Indonesian Food Science and Technology Journal, 2025)
Bignay pomace, a fruit wine byproduct, is rich in phenolics with significant potential for valorization into a functional food ingredient. However, it is prone to degradation during storage. This study investigated the effects of temperature (−20°C, 4°C, 30°C, and 40°C) and lighting conditions on the stability of phenolic compounds and antioxidant properties of freeze-dried bignay pomace obtained through an eco-friendly, water-based extraction method. Total phenolic content (TPC), DPPH radical scavenging activity, and ferric reducing antioxidant power (FRAP) were monitored over a 35-day period. Across all time points, samples at −20°C and 4°C generally retained higher TPC and antioxidant activity than those stored at 30°C and 40°C. Notable fluctuations were observed, with an early decline in the first weeks, a brief rise around Days 21–28, and a final drop by Day 35. After 35 days, TPC declined by ~18–21% at −20°C, 4°C, and 30°C, while at 40°C the reduction reached ~25%. Degradation followed zero-order kinetics, with rate constants (k) ranging from 3.2224 to 4.5207, and the slowest degradation at -20°C. DPPH activity decreased by 23–33% and FRAP by 41–64%, with the most significant losses at 40°C. Light had a moderate effect, significantly influencing DPPH scavenging activity at 4°C and FRAP at -20°C and 30°C only. Overall, temperature was the primary factor influencing degradation. Keeping the extract at low temperatures (freezing or refrigeration) is critical to preserving its phenolic content and antioxidant properties for use as a natural, clean-label ingredient, while light protection plays a secondary role.